APPLICATION OF WESTERN HARMONY IN CONTEMPORARY AND ERSTWHILE MUSIC OF INDIA - Chauhan, Mukul; Srivastava, Kinshuk (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores into the kinship between Indian music and the western music system through the application of western chords in the Hindustani classical and Indian music. This paper gives us the understanding as how to present a Hindustani classical composition with the help of western instruments like Guitar and Piano. The paper determines the relationship between the two music systems through western theory and how it is applied to the Hindustani Classical and Indian music.